Realisasi Anggaran Pendapatan Pedagang Buah Di Pasar Ciputat - Linda Permata Sari; Dita Faradilla; Muna Salsabila; Muhamad Yuzril Bimantoro; Muhammad Ryafinuddin; Saridawati Saridawati (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research employs a qualitative approach to explore the revenue realization of fruit traders at the Ciputat Market, South Tangerang City. Primary data was obtained through interviews with five fruit traders over a period of two months. The results indicate an average monthly income of Rp16.107.600 with expenditures of Rp7.610.000, resulting in an average net profit of Rp2.219.000. The analysis of the income-expenditure ratio indicates good business sustainability (R/C Ratio = 1.06). Findings also identify factors such as price fluctuations and seasons that affect outcomes. Nevertheless, fruit traders at the Ciputat Market have the potential to optimize their income with more effective pricing strategies.